Factors Associated with Japanese Encephalitis Vaccination Status during Routine Immunization among Children Aged 24-59 Months in Birendranagar Municipality, Nepal (MedS Alliance Journal of Medicine and Medical Sciences, 2021)
INTRODUCTION: Most authorities agree that the control of JE requires universal childhood immunization. JE (Japanese Encephalitis) vaccination in routine immunization coverage is low and fluctuating sometimes in Nepal. Therefore, this study conducted to understand the factors associated with the low coverage of JE.MATERIALS AND METHODS: A cross-sectional study design was conducted among children in routine immunization in Birendranagar Municipality of Nepal. Mix methods were applied to gather information from the respondents. Lottery method was used to select wards and respondents were selected randomly based on Proportionate to Population Size (PPS). Face to face interview was done with the help of structured questionnaire to the mother of children. Univariate and multivariate analysis were performed.RESULTS: Among 321 respondents of the study, the mean age of mothers of 15-44 years was 26.3 ± 4.4 years. It was found that, 20.9% (n=67) of mothers had heard about JE disease however only 15% (n=48) of the mothers had heard about JE vaccine. About 38.3% (n=123) of the mothers, reported that Female Community Health Volunteer (FCHV) were the major source of information. This study reported that the coverage of JE vaccine was 52.3% (n=168), and average age of receiving JE vaccine was 13±1.4 months.CONCLUSIONS: The findings of this study recommends that focused program should be conducted to increase the knowledge of mothers and FCHV and health workers should be mobilized as major source of information for vaccination.